Silicon-carbon negative electrode material, preparation method thereof and electrochemical device
By adding ammonia-containing tempering agents during nano-silicon grinding and combining them with organic carbon materials, the problem of volume effect of silicon negative electrode materials is solved, and the Coulomb efficiency and cycling performance of silicon carbon materials are significantly improved.
Patent Information
- Application Number
- CN202411912379.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Silicon negative electrode materials are prone to severe volume effects during the lithiation process, which limits their commercial application.
Using a silicon-carbon negative electrode material, the nano-silicon dispersion is significantly improved, the degree of oxidation is reduced, and the organic carbon material is combined to form a conductive network to alleviate volume expansion.
It effectively slows down the volume effect of nano-silicon, improves the Coulomb efficiency and circulation performance of silicon-carbon materials, and extends the cycle life of the battery.
Smart Images

Figure CN119725510A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, as well as an electrochemical device. Background Art
[0002] Lithium-ion batteries are now widely used in electric vehicles, power tools, 3C and other fields. With the rapid development of the new energy industry, higher requirements are placed on the energy density and cycle life of lithium-ion batteries. Traditional lithium-ion batteries use graphite as the negative electrode material, but the theoretical specific capacity of graphite negative electrode materials is low (372mAh / g), which cannot meet the high energy density requirements of batteries. Compared with graphite negative electrode materials, silicon negative electrode materials have higher theoretical specific capacity (4200mAh / g), lower lithium extraction / insertion potential, higher safety performance, abundant reserves and other advantages, and are gradually used as negative electrode materials for lithium-ion batteries. However, silicon negative electrode materials are prone to serious volume effects during the lithiation process, which is the biggest limitation on the commercial application of silicon negative electrode materials.
[0003] Based on the above difficulties, the industry has adopted a variety of methods to solve them, such as mixing nano-sized silicon and graphite materials in a certain proportion, compounding silicon with metal or non-metallic materials, vapor depositing nano-silicon on porous carbon materials, optimizing the structure of silicon materials (porous, nano-sized), using incomplete oxides of silicon, etc. These methods can suppress the volume effect of silicon negative electrode materials to a certain extent, but there are still some problems in commercial applications.
[0004] There are three main methods for producing silicon negative electrode materials: physical grinding, chemical vapor deposition, and plasma evaporation and condensation. Physical grinding has the advantages of low cost and scalability, and is currently the mainstream method for preparing nano-silicon in China. The nano-silicon grinding process is mostly based on a solution system, and the rotation speed is high during the grinding process, which inevitably causes the silicon material to oxidize, forming an uneven oxide layer on the surface of the silicon material. In addition, as the particle size of the silicon material decreases in the solution system, the dispersion of the nano-silicon material and the increase in the temperature of the solution system become issues that cannot be ignored in the nano-silicon production process. Solving the problems of oxidation, dispersion, temperature, etc. in the physical grinding process of nano-silicon has become the key to the process in the nano-silicon production process.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The first purpose of the present invention is to provide a silicon-carbon negative electrode material to solve the serious volume effect problem of silicon negative electrode materials. The above technical purpose of the present invention is achieved through the following technical solutions:
[0007] A silicon-carbon negative electrode material includes nano-silicon slurry and organic carbon, wherein the mass ratio of silicon material to organic carbon is 1:0.1 to 1:2; the organic carbon material serves as a buffer layer, which can effectively alleviate the volume expansion of silicon and maintain the integrity of the electrode structure, thereby extending the cycle life of the battery.
[0008] The nano silicon slurry is prepared by wet grinding and comprises micron silicon powder, dispersion liquid, dispersant, antioxidant and ammonia-containing conditioning agent, wherein the mass ratio of the micron silicon powder, dispersion liquid, dispersant, antioxidant and ammonia-containing conditioning agent is 1-4:10-20:0-1:0-1:0-1.
[0009] Preferably, the organic carbon is one or more of asphalt, polyethylene glycol, glucose, phenolic resin, sucrose, citric acid, epoxy resin, polyimide resin, bismaleimide resin, urea-formaldehyde resin, melamine resin, and formaldehyde resin. The organic carbon material can form a conductive network in the silicon negative electrode to improve the overall conductivity of the silicon material.
[0010] Preferably, the micron silicon powder is photovoltaic recycled silicon waste, industrial silicon or commercial silicon powder of different purities.
[0011] Preferably, the dispersion liquid is one or more of methanol, anhydrous ethanol, propanol, butanol, isopropanol, ethylene glycol, vinyl alcohol, deionized water, benzyl alcohol, n-butanol, cyclohexane hexol, n-butanol, and glycerol. The dispersion liquid will eventually evaporate completely through subsequent drying and will not enter the final material.
[0012] Preferably, the dispersant is one or more of water glass, sodium tripolyphosphate, sodium pyrophosphate, sodium dodecyl sulfate, hexamethyldisilazane, sodium alkyl diphenyl ether sulfonate, hexadecyltrimethylammonium bromide, sodium hexametaphosphate, polyvinyl pyrrolidone, oleic acid, triamine citrate, and polyvinyl alcohol.
[0013] Preferably, the antioxidant is one or more of gallic acid ester, trihydroxybutyrophenone, butylated hydroxyanisole, tert-butylhydroquinone, formic acid, acetic acid, tert-butylhydroquinone, ethanolamine, isohydroxy acid, glutamic acid, citric acid, propionic acid, propylene glycol, thiopropionic acid, sorbitol, dilauryl thiodipropionate, phosphorous acid, and lecithin.
[0014] Preferably, the ammonia-containing conditioning agent is one or more of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium nitrate, ammonium carbonate, ammonium bicarbonate, and ammonia water. The nitrogen-containing functional group of the ammonia-containing conditioning agent will change the surface properties of the nano-silicon material, so that its surface has a certain hydrophilicity or electrophilicity. It helps to reduce the attraction between silicon particles, thereby improving the dispersibility of silicon. It makes the silicon particles easier to disperse and reduce the particle size during wet grinding. Reducing the particle size helps to increase the specific surface area of nano-silicon, thereby increasing the contact area between silicon and organic carbon materials. In addition, the ammonia-containing conditioning agent realizes nitrogen doping on the surface of nano-silicon, thereby improving the conductivity of the material.
[0015] The second purpose of the present invention is to provide a method for preparing a silicon-carbon negative electrode material. By adding an ammonia-containing conditioning agent during the nano-silicon grinding process, the dispersion of nano-silicon is significantly improved, the nano-silicon grinding efficiency is increased, the production cost is reduced, and the oxidation of nano-silicon is reduced, thereby slowing down the volume effect of nano-silicon and improving the coulombic efficiency and cycle performance of the silicon-carbon material.
[0016] The above technical objectives of the present invention are achieved through the following technical solutions:
[0017] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0018] S01: adding the screened micron silicon powder, dispersion, dispersant, antioxidant, ammonia-containing conditioning agent and grinding medium into a sand mill for physical grinding for 4 to 10 hours to obtain nano silicon slurry;
[0019] S02: transferring the nano-silicon slurry to a disperser, and then adding organic carbon in proportion to the disperser to fully mix the nano-silicon slurry and the organic carbon;
[0020] S03: spray drying the mixed slurry to obtain nano silicon-carbon secondary agglomerate particles, crushing and sieving the nano silicon-carbon secondary agglomerate particles to obtain intermediate 1;
[0021] S04: placing the intermediate 1 in a closed sintering furnace, introducing an inert atmosphere, heating the sintering furnace to 800-1200° C. and sintering for 1-6 hours to obtain an intermediate product 2;
[0022] S05: placing the intermediate product 2 in a closed, 600-1000°C suspension environment, introducing a mixed gas, coating the intermediate product 2 for 1-6 hours, and obtaining a silicon-carbon negative electrode material.
[0023] Preferably, in S01, the grinding medium is a zirconium ball with a diameter of 0.1 mm; the physical grinding speed is 500 to 2000 rpm, and the time is 1 to 10 hours.
[0024] Preferably, in S04, the inert atmosphere is one or more of nitrogen, argon, helium, and neon.
[0025] Preferably, in S05, the mixed gas is a mixed gas of a carbon source gas and a carrier gas, wherein the carbon source gas is one or more of methane, acetylene, propylene, ethylene, ethane, acetone, butane, benzene, natural gas, toluene, and propyne, and the carrier gas is one or more of nitrogen, argon, helium, and neon, and the volume ratio of the carbon source gas to the carrier gas is 2:98 to 20:80.
[0026] The third object of the present invention is to provide an electrochemical device made of silicon-carbon negative electrode material to promote the improvement of the cycle performance of the silicon-carbon negative electrode material.
[0027] The above technical objectives of the present invention are achieved through the following technical solutions:
[0028] An electrochemical device, wherein the negative electrode material of the electrochemical device comprises the above-mentioned silicon-carbon negative electrode material, wherein the first lithium delithiation specific capacity of the electrochemical device comprising the above-mentioned silicon-carbon negative electrode material is 500mAh / g to 3000mAh / g.
[0029] The preparation method of an electrochemical device described in the present invention is as follows:
[0030] T1: Preparation of pole piece
[0031] The silicon-carbon material, carbon nanotube slurry and sodium carboxymethyl cellulose prepared above were added into deionized water in a mass ratio of 80:10:10 to prepare a slurry with a solid content of 20%. The slurry was then coated on one side of the current collector copper foil, dried in a 60°C forced air drying oven for 2 hours, and then transferred to a 80°C vacuum drying oven for 8 hours. The electrode was then cold pressed and cut into pieces for later use.
[0032] T2: Preparation of electrolyte
[0033] In a dry argon atmosphere glove box, ethylene carbonate and diethyl carbonate were first mixed at a volume ratio of 1:1 to obtain solution A, then lithium hexafluorophosphate and solution A were mixed at a concentration of 1 mol / L to obtain solution B, and 5% of fluoroethylene carbonate film-forming additive was added to solution B to obtain an electrolyte;
[0034] T3: Preparation of diaphragm, negative electrode shell, spring sheet, lithium sheet, gasket and positive electrode shell
[0035] The diaphragm is a polyethylene / polypropylene composite microporous film with a thickness of 15 μm and a diameter of 19 mm. The negative electrode shell, spring sheet, lithium sheet, gasket and positive electrode shell are CR2025 model battery accessories. The above materials are all purchased commercially.
[0036] T4: Electrochemical device assembly
[0037] The prepared electrode pieces were neatly stacked in the order of negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, electrode piece and positive electrode shell in an argon atmosphere glove box, and the electrolyte was dripped. The stacked batteries were placed in the groove on the packaging machine and packaged under a pressure of 550 kg to obtain CR2025 button-type lithium-ion batteries.
[0038] Electrochemical device testing
[0039] The battery was charged and discharged using the Wuhan Blue Electric series battery test system. First, a current of 0.1A was applied to discharge to 0V, and after standing for 3 minutes, a current of 50μA was used to discharge to 0V, and after standing for another 3 minutes, a current of 10μA was used to discharge to 0V to obtain the first discharge capacity of the silicon-carbon material, and then a current of 0.1A was used to charge to 2V to obtain the first charge capacity. The ratio of the first charge capacity to the discharge capacity is the first coulomb efficiency.
[0040] In summary, the present invention has the following beneficial effects:
[0041] 1. The present invention adds an ammonia-containing conditioning agent during the sand-grinding process. The ammonia-containing conditioning agent can provide nitrogen-containing functional groups and give nano-silicon special chemical effects, thereby changing the surface properties of the nano-silicon material, achieving the dispersion of nano-silicon in the nano-silicon slurry, and is more conducive to improving the grinding efficiency and reducing the nano-silicon particle size. This method can significantly reduce the grinding time, significantly save energy consumption, and is more conducive to commercial development;
[0042] 2. The ammonia-containing conditioning agent added in the present invention can improve the grinding efficiency, so that the time required for grinding micron silicon to the target particle size is shortened, thereby effectively reducing oxidation caused by long-term grinding and the increase in the temperature of the grinding system. The obtained nano-silicon has a low degree of oxidation, which is beneficial to improving the first coulomb efficiency of the silicon-carbon negative electrode material;
[0043] 3. The ammonia-containing conditioning agent added in the present invention can realize nitrogen doping of the silicon-carbon negative electrode material. The addition of nitrogen can improve the conductivity of the silicon-carbon negative electrode material, thereby promoting the improvement of the cycle performance of the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments in the records of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 is the nano-silicon particle size in the nano-silicon slurry in step S1 of the embodiment and the comparative example;
[0046] Figure 2 is a SEM image of the silicon-carbon material prepared in Example 2 of the present invention;
[0047] Figure 3 is a cross-sectional SEM image of the silicon-carbon material prepared in Example 2 of the present invention;
[0048] Figure 4 This is the first charge and discharge diagram of the electrochemical device prepared by the silicon-carbon material in Example 2 of the present invention;
[0049] Figure 5 This is a cycle diagram of an electrochemical device prepared using the silicon-carbon material in Example 2 of the present invention. DETAILED DESCRIPTION
[0050] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a silicon-carbon negative electrode material and a preparation method thereof and an electrochemical device proposed according to the present invention, their specific implementation methods, characteristics and effects are described in detail as follows.
[0051] Components Commercial sources Micron Silicon Powder Jiangsu Xinhua Semiconductor Technology Co., Ltd. Dispersion Shanghai Shengxi Chemical Co., Ltd. Dispersants Duoduo Chemical Reagent Network Antioxidants Duoduo Chemical Reagent Network Ammonia-containing conditioning agent Duoduo Chemical Reagent Network Organic Carbon Henan Bairun New Materials
[0052] Example 1
[0053] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0054] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium chloride, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 h to obtain nano silicon slurry;
[0055] S2: Transfer the ground nano-silicon slurry to a disperser, weigh 2 kg of asphalt and place it in the disperser, and fully mix the nano-silicon slurry and asphalt.
[0056] S3: The mixed slurry is spray-dried to obtain silicon-carbon secondary agglomerated particles, and then the silicon-carbon secondary agglomerated particles are crushed and sieved to obtain intermediate 1.
[0057] S4: placing the intermediate 1 in a closed sintering furnace, introducing an argon atmosphere, heating the sintering furnace to 1000° C. and sintering for 3 h to obtain the intermediate 2;
[0058] S5: Place the intermediate product 2 in a closed, 800°C suspension environment, introduce a mixed gas of nitrogen and acetylene at a rate of 10 L / min, wherein the volume ratio of nitrogen to acetylene is 90:10, coat the intermediate product 2 for 3 hours, and obtain a silicon-carbon negative electrode material.
[0059] The electrochemical device of the present invention is prepared by the following method:
[0060] Preparation of pole piece
[0061] The silicon-carbon material, carbon nanotube slurry and sodium carboxymethyl cellulose prepared above were added into deionized water in a mass ratio of 80:10:10 and prepared into a slurry with a solid content of 20%. The slurry was then coated on one side of the current collector copper foil, dried in a 60°C forced air drying oven for 2 hours, and then transferred to a 80°C vacuum drying oven for drying for 8 hours. The electrode was then cold pressed and cut into pieces for later use.
[0062] Preparation of electrolyte
[0063] In a dry argon atmosphere glove box, ethylene carbonate and diethyl carbonate were first mixed in a volume ratio of 1:1 to obtain solution A, and then lithium hexafluorophosphate and solution A were prepared into solution B at a concentration of 1 mol / L. 5% of fluoroethylene carbonate film-forming additive was added to solution B to obtain an electrolyte.
[0064] Preparation of diaphragm, negative electrode shell, spring sheet, lithium sheet, gasket and positive electrode shell
[0065] The diaphragm is a polyethylene / polypropylene composite microporous film with a thickness of 15 μm and a diameter of 19 mm. The negative electrode shell, spring sheet, lithium sheet, gasket and positive electrode shell are CR2025 model battery accessories. The above materials are all commercially available.
[0066] Electrochemical device assembly
[0067] The prepared electrode pieces were neatly stacked in the order of negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, electrode piece and positive electrode shell in an argon atmosphere glove box, and the electrolyte was dripped. The stacked batteries were placed in the groove on the packaging machine and packaged under a pressure of 550 kg to obtain CR2025 button-type lithium-ion batteries.
[0068] Electrochemical device testing
[0069] The battery was charged and discharged using the Wuhan Blue Electric series battery test system. First, a current of 0.1A was applied to discharge to 0V, and after standing for 3 minutes, a current of 50μA was used to discharge to 0V, and after standing for another 3 minutes, a current of 10μA was used to discharge to 0V to obtain the first discharge capacity of the silicon-carbon material, and then a current of 0.1A was used to charge to 2V to obtain the first charge capacity. The ratio of the first charge capacity to the discharge capacity is the first coulomb efficiency.
[0070] In the method for preparing silicon-carbon negative electrode materials in Examples 2 to 7 and Comparative Example 1, S2 to S5, the preparation of the pole piece, the preparation of the electrolyte, the preparation of the diaphragm, the negative electrode shell, the spring sheet, the lithium sheet, the gasket and the positive electrode shell, the assembly of the electrochemical device and the test of the electrochemical device are the same as those in Example 1. The parameters of step 1 of the method for preparing silicon-carbon negative electrode materials are changed as follows:
[0071] Example 2
[0072] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0073] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium nitrate, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 hours to obtain nano silicon slurry.
[0074] like Figure 2-3 The SEM image of the silicon-carbon material prepared in Example 2 of the present invention is shown. Figure 4 The first charge and discharge diagram of the electrochemical device prepared by the silicon-carbon material in Example 2 is shown. Figure 5 Shown is a cycle diagram of an electrochemical device prepared from silicon-carbon material in Example 2. The data show that the present invention can improve the conductivity of silicon-carbon negative electrode materials, thereby promoting the improvement of the cycle performance of silicon-carbon negative electrode materials.
[0075] Example 3
[0076] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0077] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium carbonate, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 hours to obtain nano silicon slurry.
[0078] Example 4
[0079] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0080] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium sulfate, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 hours to obtain nano silicon slurry.
[0081] Example 5
[0082] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0083] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium hydrogen sulfate, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 hours to obtain nano silicon slurry.
[0084] Example 6
[0085] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0086] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonium bicarbonate, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 h to obtain nano silicon slurry.
[0087] Example 7
[0088] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0089] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, 80 g of ammonia water, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 hours to obtain nano silicon slurry.
[0090] Comparative Example 1
[0091] The method for preparing a silicon-carbon negative electrode material according to the present invention specifically comprises the following steps:
[0092] S1: 8 kg of industrial silicon with a particle size of 50 μm after screening, 32 kg of isopropanol, 20 g of sodium alkyl diphenyl ether sulfonate, 40 g of acetic acid, and 12 kg of zirconium balls with a diameter of 0.1 mm were weighed and added into a sand mill, and the speed of the sand mill was adjusted to 1200 rpm and ground for 6 h to obtain nano silicon slurry.
[0093] The present invention provides a nano-silicon grinding formula and a method for preparing a silicon-carbon negative electrode material, wherein the particle size of the prepared nano-silicon is as follows: Figure 1 As shown, by adding an ammonia-containing conditioning agent during the physical grinding process, the dispersibility of nano-silicon in the slurry is improved, which is beneficial to improving the grinding efficiency and reducing the nano-silicon particle size, which can significantly save grinding energy consumption, reduce production costs, and promote commercialization.
[0094] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A silicon-carbon negative electrode material, characterized in that: It includes nano silicon slurry and organic carbon, and the mass ratio of silicon material to organic carbon is 1:0.1 to 1:2; The nano silicon slurry is prepared by wet grinding and comprises micron silicon powder, dispersion liquid, dispersant, antioxidant and ammonia-containing conditioning agent, wherein the mass ratio of the micron silicon powder, dispersion liquid, dispersant, antioxidant and ammonia-containing conditioning agent is 1-4:10-20:0-1:0-1:0-1.
2. A silicon-carbon negative electrode material according to claim 1, characterized in that: The organic carbon is one or more of asphalt, polyethylene glycol, glucose, phenolic resin, sucrose, citric acid, epoxy resin, polyimide resin, bismaleimide resin, urea-formaldehyde resin, melamine resin, and formaldehyde resin.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size of the micron silicon powder is 20-100 μm, and the micron silicon powder is photovoltaic recycled silicon waste, industrial silicon or commercial silicon powder of different purities.
4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The dispersion liquid is one or more of methanol, anhydrous ethanol, propanol, butanol, isopropanol, ethylene glycol, vinyl alcohol, deionized water, benzyl alcohol, n-butanol, cyclohexanehexol, n-butanol, and glycerol.
5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The dispersant is one or more of water glass, sodium tripolyphosphate, sodium pyrophosphate, sodium dodecyl sulfate, hexamethyldisilazane, sodium alkyl diphenyl ether sulfonate, hexadecyltrimethylammonium bromide, sodium hexametaphosphate, polyvinyl pyrrolidone, oleic acid, triamine citrate, and polyvinyl alcohol.
6. The silicon-carbon negative electrode material according to claim 1, characterized in that: The antioxidant is one or more of gallic acid ester, trihydroxybutyrophenone, butylated hydroxyanisole, tert-butylhydroquinone, formic acid, acetic acid, tert-butylhydroquinone, ethanolamine, isohydroxy acid, glutamic acid, citric acid, propionic acid, propylene glycol, thiopropionic acid, sorbitol, dilauryl thiodipropionate, phosphorous acid, and lecithin.
7. The silicon-carbon negative electrode material according to claim 1, characterized in that: The ammonia-containing conditioning agent is one or more of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium nitrate, ammonium carbonate, ammonium bicarbonate, and ammonia water.
8. The method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S01: adding the screened micron silicon powder, dispersion, dispersant, antioxidant, ammonia-containing conditioning agent and grinding medium into a sand mill for physical grinding for 4 to 10 hours to obtain nano silicon slurry; S02: transferring the nano silicon slurry to a disperser, and then adding organic carbon in proportion to the disperser to fully mix the nano silicon slurry and the organic carbon; S03: spray drying the mixed slurry to obtain nano silicon-carbon secondary agglomerate particles, crushing and sieving the nano silicon-carbon secondary agglomerate particles to obtain intermediate 1; S04: placing the intermediate 1 in a closed sintering furnace, introducing an inert atmosphere, heating the sintering furnace to 800-1200° C. and sintering for 1-6 hours to obtain the intermediate 2; S05: placing the intermediate product 2 in a closed, 600-1000°C suspension environment, introducing a mixed gas, coating the intermediate product 2 for 1-6 hours, and obtaining a silicon-carbon negative electrode material.
9. The method for preparing a silicon-carbon negative electrode material according to claim 8, characterized in that: In S05, the mixed gas is a mixed gas of a carbon source gas and a carrier gas, wherein the carbon source gas is one or more of methane, acetylene, propylene, ethylene, ethane, acetone, butane, benzene, natural gas, toluene, and propyne, and the carrier gas is one or more of nitrogen, argon, helium, and neon, and the volume ratio of the carbon source gas to the carrier gas is 2:98 to 20:
80.
10. An electrochemical device, wherein the negative electrode material of the electrochemical device comprises the silicon-carbon negative electrode material according to any one of claims 1 to 7, characterized in that: in, The electrochemical device comprising the silicon-carbon negative electrode material has a first lithium desorption specific capacity of 500 mAh / g to 3000 mAh / g.
Citation Information
Cited By
Preparation method of nano silicon slurry and preparation method of silicon carbon material
CN121011656A
Preparation method of nano silicon material
CN122035870A
A method for preparing a nanosilicon material
CN122035870B